In-solution structural studies involving a phospholipase A2-like myotoxin and a natural inhibitor: Plasticity of oligomeric assembly affects mechanisms of inhibition - Cardoso, Fábio F. [UNESP] (2021)
Snakebite envenomation has been categorized by World Health Organization as a category A neglected tropical disease, since it causes chronic psychological disorders, physical disablement and death. Ophidian accidents may cause local myonecrosis that cause drastic sequelae, which are not efficiently neutralized via serum therapy. Phospholipase A2-like (PLA2-like) myotoxins have a major role in the local effects caused by several snake venoms. We previously demonstrated that chicoric acid (CA) is an efficient inhibitor of the BthTX-I myotoxin and solved the X-ray structure of complex. Herein, we assess the oligomeric behavior of the BthTX-I/CA complex in solution under different physical-chemical conditions and using toxin obtained by two different biochemical methodologies to fully elucidate structural bases of inhibition of myotoxins by CA. We demonstrated the ability of PLA2-like proteins to form different oligomeric assemblies in the presence of certain inhibitors, which can also be modulated by buffer polarity change. In the presence of ethanol, BthTX-I/CA remains predominantly in a monomeric conformation, which prevents it from being in its active form (dimeric conformation). In contrast, in the absence of ethanol, the tetramer assembly was observed, which hid key regions of the protein responsible for docking and disruption of the muscle membrane. Therefore, the “plasticity” of these proteins with regard to their abilities to form oligomeric assemblies is a key issue for the future development of therapeutic agents to complement of serum therapy.